Intravesical treatment with highly-concentrated hyaluronic acid and chondroitin sulphate in patients with recurrent urinary tract infections: Results from a multicentre survey - Cicione, Antonio; Cantiello, Francesco; Ucciero, Giuseppe; Salonia, Andrea; Torella, Marco; De Sio, Marco; Autorino, Riccardo; Romancik, Martin; Tomaskin, Roman; Damiano, Rocco (Canadian Urological Association Journal, 2014)
Introduction: We assess the effectiveness of intravesical instillation of hyaluronic acid (HA) and chondroitin sulphate (CS) as a non-antibiotic treatment option for prophylaxis of recurrent urinary tract infections (UTIs) in female patients. Methods: This was a retrospective cohort study involving 7 European institutions. We included patients with recurrent UTIs who received intravesical instillations of Ialuril (IBSA International) (50 mL HA 1.6% and CS 2% solution) between January 2010 and March 2012. Medication schedule, length of follow-up, recurrence infection time, number of UTIs/patients/year, patient quality of life, subjective symptoms score, and treatment-emergent side effects were recorded and analyzed. Results: In total, 157 women (mean age: 54.2 ± 4.1 years) were included in the analysis. All patients had at least 12 months follow-up. After 4 weekly and 5 monthly HA-CS bladder instillations, UTI episodes decreased from 4.13 ± 1.14 to 0.44 ± 0.50 (p = 0.01) at 12 months, while recurrent UTI time prolonged from 94.8 ± 25.1 days to 178.4 ± 37.3 days (p = 0.01) at 12 months. An improvement in symptoms and quality of life was achieved. A medium-depth pain after medication instillation was the most reported side effect. Regression model analysis showed significant risk factors in developing new UTI episodes: being more than 50 years old and having more than 4 UTI episodes per year (OR 3.41; CI 95%; 1.51-7.71, p = 0.003 and OR 3.31; CI 95% 1.51-7.22; p = 0.003, respectively). Retrospective design and lack of a control group represent two main limitations of the study. Conclusions: Restoring glycosaminoglycans bladder layer therapy is a promising non-antibiotic therapy to prevent recurrent UTIs.